A multiple metrics approach to prioritizing strategies for measuring and managing reactive nitrogen in the San Joaquin Valley of California. (13th June 2016) - Horowitz, Ariel I; Moomaw, William R; Liptzin, Daniel; Gramig, Benjamin M; Reeling, Carson; Meyer, Johanna; Hurley, Kathleen
Abstract: Human alteration of the nitrogen cycle exceeds the safe planetary boundary for the use of reactive nitrogen (Nr). We complement global analysis by analyzing regional mass flows and the relative consequences of multiple chemical forms of Nr as they 'cascade' through multiple environmental media. The goals of this paper are (1) to identify the amounts of Nr that flow through a specific nitrogen rich region, (2) develop multiple metrics to characterize and compare multiple forms of Nr and the different damages that they cause, and (3) to use these metrics to assess the most societally acceptable and cost effective means for addressing the many dimensions of Nr damage. This paper uses a multiple metrics approach that in addition to mass flows considers economic damage, health and mitigation costs and qualitative damages to evaluate options for mitigating Nr flows in California's San Joaquin Valley (SJV). Most analysis focuses attention on agricultural Nr because it is the largest flow in terms of mass. In contrast, the multiple metrics approach identifies mobile source Nr emissions as creating the most economic and health damage in the SJV. Emissions of Nr from mobile sources are smaller than those from crop agriculture and dairy in the SJV, but the benefits of abatement are greater because of reduced health impacts from air pollution, and abatement costs are lower. Our findings illustrate the benefit of a comprehensive multiple metrics approach to Nr management.